Development of interactive software (statics) - Chan, Keith Shao Wen (2015)
Readers of this report will have an understanding of the purpose of this project, its scope, schedule and time taken to work on different parts of the project and integrate them into a complete software for education purpose. Readers can have a reference on the availability and suitability of software for development of this project should they intend to work on something similar. The basic theories and knowledge of statics are explained and problems solving guides are shown. More complex problems and solving methods are included as well. The software developed in this project contains three main parts: Lecture Materials, Exercise and Beam Analyser. The Lecture Materials and Exercise Sections are for educational and/or self-study purposes by imparting statics knowledge and problem solving methods for users to apply what they have learnt. As the major part of the whole software, the Beam Analyser is developed to tackle problems in determining reaction forces and plotting shear force diagram and bending moment diagram of a beam subjected to various loadings and support conditions. The layout and some working principles of the software are also explained, which uses some of the methods mentioned in statics theories and concepts. Second and third year students of Nanyang Technological University from School of Mechanical and Aerospace Engineering are some of the potential users that would benefit from this report and software.